2017
DOI: 10.3390/su9081373
|View full text |Cite
|
Sign up to set email alerts
|

Using Government Resettlement Projects as a Sustainable Adaptation Strategy for Climate Change

Abstract: Abstract:Given that increasing migration has been addressed as a major consequence of climate change, a growing number of scholars suggest that the planned relocation of people or Government Resettlement Projects (GRPs) should be included in climate change adaptation. This paper reviews the status of climate change and environmentally induced migration in China, and then presents an empirical case study in Shangnan County in northwest China, where a specific GRP called the 'Massive Southern Shaanxi Migration P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Articles about Ningxia claim that resettlement is an important adaptive measure for drought (Yang et al, 2015), but it is only very recently that these projects took into account the long-term viability of resettlement sites (Zheng et al, 2016). This same study actually found that resettlement disproportionately burdened the most vulnerable groups: the poor, people left behind and some new migrants (Lei et al, 2017). The burgeoning natural hazards and disaster literature in China has found resettlement to result in generalised impoverishment (Chen et al, 2017) and disproportionately burdened the most vulnerable (Guo and Kapucu, 2017).…”
Section: Resettlement and Climate Justicementioning
confidence: 85%
See 2 more Smart Citations
“…Articles about Ningxia claim that resettlement is an important adaptive measure for drought (Yang et al, 2015), but it is only very recently that these projects took into account the long-term viability of resettlement sites (Zheng et al, 2016). This same study actually found that resettlement disproportionately burdened the most vulnerable groups: the poor, people left behind and some new migrants (Lei et al, 2017). The burgeoning natural hazards and disaster literature in China has found resettlement to result in generalised impoverishment (Chen et al, 2017) and disproportionately burdened the most vulnerable (Guo and Kapucu, 2017).…”
Section: Resettlement and Climate Justicementioning
confidence: 85%
“…This is partly driven by a joint UK-Swiss-PRC project called Adapting to Climate Change in China, now in its second phase. Others working at the interface of poverty alleviation and disaster prevention have argued that government-led resettlement projects are adaptive because they reduce exposure to hazards, enable mobility, provide financial incentives, and improve living standards and psychological wellbeing (Lei et al, 2017). If there are vulnerability assessments, these are done at the county level (Zheng et al, 2016), which is inadequate for understanding vulnerability or informing planning in China because of significant inequality between and within villages.…”
Section: Resettlement and Climate Justicementioning
confidence: 99%
See 1 more Smart Citation
“…of access to land and common property resources, social networks, livelihoods) and damages that result (Barnett and O'Neill 2011;Adger et al 2012;McMichael et al 2012). A key aspect determining the extent of adverse outcomes of the relocation process hinges on the voluntary nature of relocation efforts (Barnett and O'Neill 2011;Lei et al 2017). A key aspect determining the extent of adverse outcomes of the relocation process hinges on the voluntary nature of relocation efforts (Barnett and O'Neill 2011;Lei et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Even those making the case that planned resettlement is adaptation admit that it is not the case for all those involved and for some groups it is maladaptive (Lei et al 2017). A key aspect determining the extent of adverse outcomes of the relocation process hinges on the voluntary nature of relocation efforts (Barnett and O'Neill 2011;Lei et al 2017). It is perhaps with increasing voluntariness and community control over the decision-making process (when, how, where, who and what) that provides some potential for planned resettlement to shift towards the adaptation end of the spectrum.…”
Section: Resultsmentioning
confidence: 99%